Geography - Widdowson, John; Blackshaw, Rebecca; King, Meryl; Oakes, Simon (Dynamic learning, 2020)
Exam board: AQA Level: GCSE Subject: Geography Equip your students for AQA GCSE (9-1) Geography with our fully revised second edition Student Book. Our expert author team, John Widdowson, Rebecca Blackshaw, Meryl King, Sarah Wheeler, Simon Oakes and Michael Witherick bring you new and revised examples and a wealth of new practice questions to help your students apply their knowledge to succeed at GCSE. - Enables students to learn and practice geographical, mathematical and statistical skills through engaging activities specifically designed for the 2016 curriculum - Develops students' skills responding to a range of questions with topic-specific Question Practice in each section, supplemented by practical insight from skilled teachers with examining experience - Incorporates possible fieldwork enquiries throughout with expert advice on the fieldwork assessment from authors specialising in this key area - Reduces your research time using the up to date contemporary case studies featuring UK and international examples - Features new examples and fully up-to-date statistics and examples, equipping you to teach a thoroughly contemporary course.